Domestic violence: Evidence-based policies before and during the pandemic in Greece - Artinopoulou Vasiliki (Temida, 2021)
Domestic violence and gender-based violence has been studied and recognised for many years in Greece. Adequate legislation on the criminalization of domestic violence has been implemented since 2006 (Law 3500/2006 on the Confrontation of Domestic Violence). A network of support services has also operated across the country for many years, staffed with professionals trained in the gender-sensitive perspective. However, Greece still faces the impact of the economic crisis that started in 2010 and the critical aspects of the crisis from the reduction of the public budget imposed by the European institutions in the lives of the individuals, the victims and the providers of the social services have not been fully assessed yet. The COVID-19 pandemic created problems in the victims’ access to social services and not only. The shadow pandemic describes the alarm on the increase of domestic violence during the pandemic and the isolation of the victims from the providers of social and psychological support. Addressing both the issue of domestic violence through a victim-centered approach before and during the pandemic in Greece and the need for the implementation of evidence-based policies are the general aims of the paper. To this, we present few findings from an original victimological online research on domestic violence during the first lockdown in the country (March to May 2020) and we justify the need for the implementation of evidence-based policies in the criminal justice system in Greece.